2009
DOI: 10.1111/j.1365-2567.2008.02910.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the recognition and functional heterogeneity exhibited by cytokine‐induced killer cell subsets against acute myeloid leukaemia target cell

Abstract: Summary The polyclonal cytokine‐induced killer (CIK) cells exhibit potent cytotoxicity against a variety of tumour cells including autologous and allogeneic acute myeloid leukaemic (AML) targets. At maturity, three lymphocyte subsets: CD3− CD56+, CD3+ CD56− and CD3+ CD56+, constitute the bulk of the CIK cell culture. The CD3− CD56+ subset behaves like classical natural killer (NK) cells where cytotoxicity is potentiated by blocking the human leucocyte antigen Class I molecules in the AML targets. Both the CD3+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 31 publications
6
49
0
Order By: Relevance
“…The small NK subset within the bulk CIK culture complements T cells in the killing of targets that may escape T-cell surveillance by downregulation of Class I Ag. 36 By complement-and Ab-dependent cytotoxicity mediated by NK subset within CIK culture, it was recently shown that combination with anti-CD20 Ab further enhanced their anti-lymphoma activity. 37 Other strategies include timing of infusion to coincide with nadir of lymphopenia for maximal homoeostatic expansion of adoptively transferred T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The small NK subset within the bulk CIK culture complements T cells in the killing of targets that may escape T-cell surveillance by downregulation of Class I Ag. 36 By complement-and Ab-dependent cytotoxicity mediated by NK subset within CIK culture, it was recently shown that combination with anti-CD20 Ab further enhanced their anti-lymphoma activity. 37 Other strategies include timing of infusion to coincide with nadir of lymphopenia for maximal homoeostatic expansion of adoptively transferred T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The sorted NK cell fraction (CD3 − CD56 + ) behaves like classical NK cells and the killing of autologous acute myeloid leukemia (AML) target cells mediated by these cells can be enhanced by blocking the HLA class I molecules on the target cells [12]. The CD3 + CD56 + subset, termed non-MHC-restricted T cells, is able to kill both autologous and allogeneic susceptible tumor targets such as primary AML cells of disparate HLA types [11].…”
Section: Functional Phenotypic and Genotypic Characterization Ofmentioning
confidence: 99%
“…These CD3 + CD56 + cells have been termed cytokine-induced killer cells (CIK cells) and it was shown that they possess enhanced cytotoxicity against various tumor cells (23). In contrast to NK-like T cells that are de novo, CIK cells are generated following in vitro culturing (24,25 (27,28). To our knowledge, this is the first study of this cell population investigating the relationship between the peripheral blood CD3 + /CD16 + CD56 + cells and clinical outcome in newly diagnosed patients with CLL.…”
Section: Introductionmentioning
confidence: 99%